Macroeconomic effects of personal and functional income inequality: Theory and empirical evidence for the US and Germany - Franz J. Prante (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
This paper presents a simple illustrative post-Kaleckian model of distribution and growth that incorporates personal income inequality and interdependent social norms. The model shows in an easily accessible manner how personal and functional income inequality can potentially have contrary effects on aggregate demand and growth. It can illustrate some of the major domestic developments that took place in different countries in the decades prior to the Great Recession and which were connected to inequality and country specific consumption and saving behaviour. Furthermore, aggregate consumption functions are estimated for the United States and Germany. The finding of previous studies regarding a higher elasticity of aggregate consumption with respect to wage income than with respect to profit income is confirmed. We find positive long-run effects of personal income inequality on consumption in the US. The effect is strongest for the top 10% income share and the Gini index and less strong for the top 5% and 1% income shares. While this is evidence for relative consumption patterns, it also supports the view that the 'super rich' are a somewhat distant strata for most people - questioning the notion of expenditure cascades from the very top to the very bottom of the distribution. For Germany, we fail to find compelling evidence for substantial effects of personal income distribution.
Keywords: C22; D31; D33; E11; E12; E25; 330; Income inequality; Personal and functional income distribution; Demand and growth regimes; Relative income hypothesis; Kaleckian model